Analysing stormwater temperature at site-specific discharge points along the Liesbeek River, South Africa - Crisp, Annesley (Department of Environmental and Geographical Science, 2017)
Increased urban development has resulted in increased impervious landcover and the removal of natural vegetation. The continued anthropic modification of the Earth's surface towards an urban state, has had profound effects on the surrounding natural systems (Thompson et al., 2008). Consequently, recent studies have highlighted a strong link between expanding urbanisation and thermal impacts on streams and rivers draining urban catchments (Roa-Espinosa et al., 2003; Arrington, 2003; Herb et al., 2009b). Anthropogenic perturbations such as thermal pollution can adversely disturb the natural thermal regime of a river (Boothe and Bledsoe, 2009). An important source of thermal pollution is thermally enriched stormwater runoff. During a rainfall event, runoff temperature is elevated as it makes contact with, and passes over surfaces which have a large heat storage capacity, such as pavements, roofs and roads (Young et al., 2013). However, the extent of impervious surfaces and resulting thermal pollution produced by them is poorly understood, although it is thought to be a major contributor to stream degradation. Previous research has focused on investigating the thermal effects of removing riparian vegetation. Additionally, a recent research approach has been to develop models of the urban surface-water-atmosphere systems. Finally, research in the field of fresh-water ecology has investigated the effects of temperature on aquatic biota. Water temperature affects all aspects of freshwater ecosystems and plays an important role in regulating physical and biological characteristics of a river (Olsen et al. 2011). Consequently, any anthropogenic modification to temperature can have devastating effects on the ecological functioning of a river and biodiversity of species within the river habitat. Important findings by Young et al. (2013) suggest the need for a detailed study of stormwater temperature changes in relation to rainfall events, at a catchment scale. Furthermore, data is required to show the point source effects of stormwater runoff from impervious surfaces on the temperature of the receiving water body. Therefore, the aim of this study is: To determine the extent and risk of thermal pollution at site specific discharge points, along the Liesbeek River. In order to achieve this aim, variables which cause temperature variations needed to be identified. The primary research method makes use of Thermocron iButton Temperature Loggers. These were placed in four stormwater outlet pipes, which frequently discharge event-based stormwater runoff into the Liesbeek River. Additionally, iButton loggers were placed in the river channel, to provide a reference temperature to compare stormwater discharge temperature. In addition, hourly rainfall and air temperature was acquired from the South AfricanWeather Service (SAWS) and was used in conjunction with the iButton temperature data.